CHARACTERIZATION OF THE CLINICAL URGENCY CARE VISITS IN A HABITUAL RISK MATERNITY HOSPITAL: A CROSS-SECTIONAL STUDY - Tatiane Herreira Trigueiro; Kauane Vicari; Karoline da Luz Janiacki; Ana Paula da Rosa; Fernanda Karine Kissula (Universidade Federal do Paraná, 2022)
Objective: to characterize the emergency care services offered in a habitual risk maternity hospital. Method: a quantitative, cross-sectional and retrospective research study, with analysis of the indicators corresponding to the emergency care services of a maternity hospital from a capital city in southern Brazil, from January 2018 to December 2019. The data were subjected to descriptive analysis. Results: of the 25,451 care visits, 24,307 corresponded to pregnant women, 944 were puerperal women, 119 had undergone miscarriages, 46 are not pregnant, and 35 cases were undefined. The mean number of visits per month was 1,060; with greater demand in the afternoon shift, in the age group between 20 and 29 years old, with a minimum of eight and a maximum of 61 years old; with third trimester of pregnancy and green urgency risk rating representing higher demand. The most frequently recorded reason to seek care was abdominal pain. Conclusion: the research contributed to understanding in which Health Care Network services communication should be strengthened, improved and maintained.